MICROARTROPODOS EN SISTEMAS URBANOS (Acta Entomológica Chilena, 2022)
The soil microarthropod fauna was studicd in the urban park Balmaceda, in Santiago, Chile.A total of 61 samples were taken under five contrasting situations, namely grass (formed by acomplex of species), a shrubby plant Ligusirum sinensis and three species of tree namely,Cryptocarya alba, Quercus súber and Erythrina umbrosa. Litter or soil samples of 250 mi wereworked out, treated in Berlese-Tullgren funnels.The average densities for each higher laxa and their standard deviations are given, as well as therelative abundance and the presence frequencies in the samples. The total amount of recordedmaterial adds up to 14697 individuáis, distributed in 25 higher laxa of soil microarthropods.Also presented are the results of the analysis of variance, to test the influence of the factors"plant growth form” and "tree species" on the abundance of the 7 taxa wilh higher samplefrequencies. The plant growth form factor, showed a significant influence over the abundances ofmost of the analyzed taxa and total fauna. The tree species factor showed little influence, beingsignificant only for Tarsonemid mites and total fauna.The densities and relative abundance were compared with those of some chilean naturalecosystems. The absoluto abundance is higher in park than those in meadows and steppes, but lowerto that from forests and tundra. The low proportion of inseets and the high percentage of Tarsonemidand Acaridida mites was a characteristic in the urban park.This material in urban parks, easely accesible, is thought to be useful in the achievemenl ofvarious educational and research objectives, whether be invertebrate zoology or ecology.
Keywords: Soil fauna, Microarthropods, Urban parks, Influence of plant species, Influence of plant growth form